2016
DOI: 10.4103/0976-0105.189435
|View full text |Cite
|
Sign up to set email alerts
|

Use of simulated patient approach to assess the community pharmacists′ knowledge of appropriate use of metered dose inhaler

Abstract: Rationale:The pharmacist charged with the responsibility of drug administration and counseling should have the basic knowledge and skills necessary to demonstrate the use of metered dose inhalers (MDIs) to asthma patients for the maximization of treatment outcomes.Objective:This study was designed to evaluate the community pharmacists’ knowledge of the appropriate use of MDIs in Anambra State, Nigeria.Methods:The study was carried out in two major cities in Anambra State, Nigeria, using 41 registered community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 12 publications
(18 reference statements)
3
10
0
Order By: Relevance
“…Among essential steps, begin breath in slowly and actuate the canister once, were the most skipped step in our findings, which is quite comparable to the Ethiopian study in Mekele [ 20 ]. However, in the Nigerian study, this step was demonstrated usually by the practicing pharmacists (90.2%) [ 19 ]. While a study conducted in Iran revealed that “depressing the canister” was the repeatedly occurring error [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among essential steps, begin breath in slowly and actuate the canister once, were the most skipped step in our findings, which is quite comparable to the Ethiopian study in Mekele [ 20 ]. However, in the Nigerian study, this step was demonstrated usually by the practicing pharmacists (90.2%) [ 19 ]. While a study conducted in Iran revealed that “depressing the canister” was the repeatedly occurring error [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study done in Nepal on nurses, physicians and pharmacists concluded as healthcare professionals MDI use were poor before intervention and intervention has took the lion share in changing the existing trend to a better practice [ 18 ]. A simulated client based study done in Nigeria generalized that community pharmacists lack the knowledge and skill of demonstrating basic steps in proper use of MDI [ 19 ]. In a study done in Mekelle, Ethiopia, MDI technique of pharmacy professionals was very limited [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…11,14 Previous attention has been largely on assessing patients' knowledge of inhaler technique, 10,15,16,17 in the management of asthma and achieving optimal asthma control, however there are few studies in Nigeria that evaluated the care givers' knowledge of inhaler technique. 18,19 The effectiveness of inhalers in the care of asthma and other airway disease is often dependent on proper knowledge and communication of the correct technique by the health care giver. The purpose of this study was to assess the knowledge of doctors and nurses in a tertiary hospital in south-west Nigeria regarding spacer devices, peak flow meters and inhaler techniques.…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence has shown that many pharmacists and other healthcare professionals lack the skills necessary to appropriately counsel patients on inhaled devices. [10][11][12][13][14][15][16] Currently, it is unclear how inhaler technique of pharmacists can be enhanced; therefore, the aim of this systematic review was to focus on evaluating the effects of educational interventions on community pharmacists knowledge of inhaler technique.…”
Section: Introductionmentioning
confidence: 99%